Chromium exposure disrupts chromatin architecture upsetting the mechanisms that regulate transcription. Issue 9 (June 2019) - Zablon, Hesbon A; VonHandorf, Andrew; Puga, Alvaro
Hexavalent chromium (Cr(VI)) is a highly mutagenic and carcinogenic chemical used in many industrial processes. Occupational exposure to chromium, occurring mostly by inhalation, constitutes a major lung cancer risk affecting chromium workers. Environmental exposure, on the other hand, mainly by ingestion of contaminated drinking water, is a widespread gastrointestinal cancer risk, affecting millions of people throughout the world. One of the major mechanisms through which Cr(VI) causes carcinogenic transformation is thought to be the disruption of transcriptional regulation. Indeed, Cr(VI)-directed DNA damage and crosslinking occurs preferentially at sites where active DNA replication and transcription processes take place. Accordingly, numerous studies have shown that Cr(VI) causes gene expression changes in a wide range of cell signaling pathways, resulting from Cr(VI)-induced direct macromolecular damage, alteration in transcription factor function, and disruption of epigenetic signatures. This brief review highlights past and current information on the impact of Cr(VI) on the various mechanisms of transcriptional regulation. Impact statement: This mini-review highlights current evidence on the mechanisms through which hexavalent chromium (Cr(VI)) disrupts transcriptional regulation, an emerging area of interest and one of the central processes by which chromium induces carcinogenesis. Several studies have shown that Cr(VI) causes widespread DNA damage and disrupts epigenetic signatures, suggesting that chromatin may be a direct Cr(VI) target. The findings discussed here suggest that Cr(VI) disrupts transcriptional regulation by causing genomic architecture changes.